2007
DOI: 10.1111/j.1365-2443.2007.01079.x
|View full text |Cite
|
Sign up to set email alerts
|

Two‐step, extensive alterations in the transcriptome from G0 arrest to cell division in Schizosaccharomyces pombe

Abstract: Body cells in multicellular organisms are in the G0 state, in which cells are arrested and terminally differentiated. To understand how the G0 state is maintained, the genes that are specifically expressed or repressed in G0 must be identified, as they control G0. In the fission yeast Schizosaccharomyces pombe, haploid cells are completely arrested under nitrogen source starvation with high viability. We examined the global transcriptome of G0 cells and cells on the course to resume vegetative growth. Approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
92
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(101 citation statements)
references
References 55 publications
(69 reference statements)
7
92
0
2
Order By: Relevance
“…The isp7 ϩ gene was originally isolated during a screen for genes that show increased transcription under nitrogen starvation conditions (41). ⌬isp7 mutant cells are viable but lose viability following heat shock during the stationary phase (42). We found that while overexpression of isp7 ϩ suppressed the sensitivity of ⌬tsc1/2 mutant cells to rapamycin, deletion of isp7 ϩ in the background of ⌬tsc1 or ⌬tsc2 cells resulted in double mutant cells that were unable to grow on proline plates (Fig.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The isp7 ϩ gene was originally isolated during a screen for genes that show increased transcription under nitrogen starvation conditions (41). ⌬isp7 mutant cells are viable but lose viability following heat shock during the stationary phase (42). We found that while overexpression of isp7 ϩ suppressed the sensitivity of ⌬tsc1/2 mutant cells to rapamycin, deletion of isp7 ϩ in the background of ⌬tsc1 or ⌬tsc2 cells resulted in double mutant cells that were unable to grow on proline plates (Fig.…”
Section: Resultsmentioning
confidence: 80%
“…2D) and the presence of feedback loop mechanisms may explain this paradoxical behavior of isp7 ϩ . Finally, disruption of isp7 ϩ results in an inability to acquire normal stationary-phase physiology, which is manifested by the inability of the cells to withstand heat shock under stationary (nondividing/G 0 -like) conditions (42,62). The long-term viability of nondividing cells is also known as chronological longevity (63).…”
Section: Fig 10mentioning
confidence: 99%
“…The FACS patterns shown in Figure 3A (right) indicate that the onset of DNA replication occurred around 6 hr, and the first mitosis at 8 to 10 hr, consistent with previous results. 24,25 The level of Rad21 in G 0 was comparable to that in VE and appeared to be hyper-phosphorylated. In our previous report, the level of Rad21 in G 0 was much lower than that in VE.…”
Section: Resultsmentioning
confidence: 85%
“…To determine whether Rad21 can be directly phosphorylated by Rad3/ATR, we performed an in vitro assay of Rad3/ATR tagged with GST and 25 and then released by adding nitrogen source at 26°C. The phosphorylation level of T147, S165 and S507 was assessed by phospho-specific antibodies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation